Uma experiência de formação continuada de professores no cotidiano escolar. Um estudo de caso - Maboni, Pedro Luiz (2004)
This study tried to know the results of an experience with the teacher s education that occurs continually. This kind of education is carried out in the Colégio Estadual Tancredo Neves an elementary school from the state public service of Santa Maria. The study focused the analysis of teacher s opinion about the program of education that occurs continually as well as about the improvements of school practice and quality of teaching. The school offers this program and the study was developed from the diagnosis done by the school. According to the teachers and board of directors statements the indicators of satisfaction about activities that were being developed in this school were considered very difficult. It is important to remember that case study was the method of investigation used whose individuals were teachers and the board of directors. Through semi-structured interviews the individuals had the opportunity to demonstrate their opinions about questions related to the program of education that occurs continually, about their involvement with the program and its importance to the improvement of teaching and school practice. In this way, teachers could do an auto-evaluation and an evaluation of conditions in which they teach as well as to evaluate the results reached in the body of indicators of teaching quality and teacher s work satisfaction. The reached results were encouraging because it was possible not only to signify this research in the pedagogic field but also to understand that school can and must be an excellent space of reflection and a permanent education for teachers.